2022
DOI: 10.51821/85.2.10100
|View full text |Cite
|
Sign up to set email alerts
|

Belgian consensus on irritable bowel syndrome

Abstract: Background: Irritable bowel syndrome (IBS) is characterised by recurrent abdominal pain related to defaecation or associated with altered stool frequency or consistency. Despite its prevalence, major uncertainties in the diagnostic and therapeutic management persist in clinical practice. Methods: A Delphi consensus was conducted by 20 experts from Belgium, and consisted of literature review and voting process on 78 statements. Grading of recommendations, assessment, development and evaluation criteria were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 274 publications
0
8
0
Order By: Relevance
“…Furthermore, the evaluation of IBS symptom improvement using the IBS Symptom Severity Scale (IBS-SSS) and IBS Quality of Life (IBS-QoL) scores revealed signi cant improvements in the LF-GFD group compared to the control group. This indicates that LF-GFD intervention not only reduces speci c symptoms but also enhances overall well-being and quality of life in IBS patients [19] . These ndings are consistent with previous studies that have reported the bene cial effects of a low-FODMAP diet in IBS management.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the evaluation of IBS symptom improvement using the IBS Symptom Severity Scale (IBS-SSS) and IBS Quality of Life (IBS-QoL) scores revealed signi cant improvements in the LF-GFD group compared to the control group. This indicates that LF-GFD intervention not only reduces speci c symptoms but also enhances overall well-being and quality of life in IBS patients [19] . These ndings are consistent with previous studies that have reported the bene cial effects of a low-FODMAP diet in IBS management.…”
Section: Discussionmentioning
confidence: 81%
“…Continuous variables following a Gaussian distribution were expressed as mean (standard deviation) and analyzed using unpaired t-tests (Rome positive versus Rome negative) or oneway ANOVA (IBS-D versus IBS-C versus IBS-M versus IBS-U). Non-parametric continuous variables were expressed as median (range) and analyzed with Mann-make lifestyle changes with sufficient sleep, relaxation, and physical exercise (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by recurrent abdominal pain and discomfort associated with altered bowel habits that occur in the absence of structural and biochemical alterations or other organic gastrointestinal (GI) diseases [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%